Análise do bem-estar materno e da assistência prestada em uma unidade de pré-parto/parto/pós-parto imediato - Alvares, Aline Spanevello (2017)
The 20th Century was marked by the occurrence of paradigmatic changes related to the ways of conducting a birth. Due to the emergence and indiscriminate interventionist practices, the normal childbirth stopped being conceived as a natural physiological event, becoming understood as an event that requires intervention of different orders, like surgical or with drugs. That is a fact that determined different repercussions on society, such as: The emergence of innumerable questionings about this issue by the scientific community. This way, the present study aimed at analyzing the maternal welfare in a birthing situation, through analysis of the assistance provided in the labor passing, partum and immediate postpartum and neonatal, and the measurement of this PPP unit patients’ welfare. The present project is a transversal descriptive study featuring a quantitative approach, that included all the normal births that happened in the period of June to September, 2016, totaling 104 parturients. The information was gathered through a data collection tool with questions related to identification and sociodemographic information, obstetric background, obstetric data related to passing of the current birth, data related to the newborn, which were collected through an interview with the puerpera and through data from the medical records, and at last, data related to these women’s welfare. For the last one, a scale of maternal welfare in birthing situation was used. This scale was produced by Chilian obstetric nurses, adapted culturally and its psychometric properties was translated and validated into Portuguese Language. To analyze this data, the descriptive and bivariate analysis and also the logistical regression were practiced by means of the Program Epi-Info version 7.0. The project was submitted to the Research Ethics Committee at Júlio Muller University Hospital with final approval under the number 1.571.789 on June 2nd, 2016. The results showed that many practices considered to be humanized were performed, however, invasive technologies also were discovered. Regarded to welfare, the study showed that 76% of the women had good health. The variables that showed statistically significant association with the results of scale of maternal welfare in birthing situation were: non-invasive technologies, amniotomy, and position during labor and birth and skin-to-skin contact. We could notice that the results referring to the humanized practices, performed at this hospital, were satisfactory, however, it is still necessary to review some practices.